Pemanfaatan Teknologi Informasi sebagai Sumber Belajar untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di SD Negeri 05 Ipuh - Ali Mustaqimuddin (UNISAN JURNAL, 2024)
Islamic religious education in elementary schools is an integral part in forming students’ character and spirituality. However, challenges arise in teaching this subject in a method that is engaging and effective for students. This research aims to explore the use of information technology as a learning resource in improving student learning outcomes in Islamic Religious Education subjects at SD Negeri 05 Ipuh. The research method used was classroom action research involving 30 grade 4 students as research subjects. Utilization of information technology is carried out through the use of interactive and multimedia software specifically designed for learning Islamic Religious Education. Data was collected through observation, learning results tests, and interviews with teachers and students. The research results show that the use of information technology as a learning resource can improve student learning outcomes in Islamic Religious Education subjects. There is a significant increase in students’ understanding of concepts, interest in learning, and active participation during the learning process. Apart from that, the use of information technology also provides variations in learning approaches and increases student involvement in learning activities. These findings indicate that the integration of information technology in Islamic Religious Education learning at SD Negeri 05 Ipuh has great potential to improve learning effectiveness and student learning outcomes. The practical implication of this research is the need for further support in the development and application of information technology in the context of religious learning at the elementary level to support better achievement of educational goals.